Prostaglandin E2 Exerts Biphasic Dose Response on the PreBötzinger Complex Respiratory-Related Rhythm - Reising, Jan Philipp; Phillips, Wiktor S.; Ramadan, Naify; Herlenius, Eric (Frontiers in Neural Circuits, 2022)
Inflammation in infants can cause respiratory dysfunction and is potentially life-threatening. Prostaglandin E2 (PGE2) is released during inflammatory events and perturbs breathing behavior in vivo. Here we study the effects of PGE2 on inspiratory motor rhythm generated by the pre-Bötzinger complex (preBötC). We measured the concentration dependency of PGE2 (1nM-1µM) on inspiratory-related motor output in rhythmic medullary slice preparations. Low concentrations (1-10nM) of PGE2 increased the duration of the inspiratory burst period, while higher concentrations (1µM) decreased the burst period duration. Using specific pharmacology for prostanoid receptors (EP1-4R, FPR, DP2R), we determined that coactivation of both EP2R and EP3R is necessary for PGE2 to modulate the inspiratory burst period. Additionally, biased activation of EP3 receptors lengthened the duration of the inspiratory burst period, while biased activation of EP2 receptors shortened the burst period. To help delineate which cell populations are affected by exposure to PGE2, we analyzed single-cell RNA-Seq data derived from preBötC cells. Transcripts encoding for EP2R (Ptger2) were differentially expressed in a cluster of excitatory neurons putatively located in the preBötC. A separate cluster of mixed inhibitory neurons differentially expressed EP3R (Ptger3). Our data provide evidence that EP2 and EP3 receptors increase the duration of the inspiratory burst period at 1-10nM PGE2 and decrease the burst period duration at 1µM. Further, the biphasic dose response likely results from differences in receptor binding affinity among prostanoid receptors.